Profilaksis vs. Terapi Preemtif Penyakit Cytomegalovirus (CMV) pada Pasien Transplantasi Ginjal Risiko Tinggi: Suatu Laporan Kasus Berbasis Bukti - Wardhani, Ariani Intan; Tunjungputri, Rahajeng N.; Tetrasiwi, Erpryta Nurdia; Marbun, Maruhum Bonar (UI Scholars Hub, 2023)
Kidney transplant recipients require the use of immunosuppressive agents to prevent multiple organ rejection. Administration of immunosuppressive agents triggers an increased risk of impaired immunity and microbial infections, one of which is cytomegalovirus (CMV). Prevention of cytomegalovirus infection can be given as a prophylaxis or preemptive therapy. However, the efficacy of choosing prophylaxis or preemptive therapy is still under debate, thus we conducted this study to identify current approach in preventing CMV disease in clinical practice. A literature search was carried out using the PubMed, Cochrane Library, Embase and Scopus databases with the keywords “high risk kidney transplant”, “prophylaxis”, “preemptive” and “CMV infection disease”. Inclusion criteria were only studies in adult kidney transplant patients as a population. , prophylaxis as intervention, preemptive therapy as comparison, and cytomegalovirus infection as outcome. The exclusion criteria of this study were the study articles that were not in Bahasa Indonesia or English, case reports and studies with subjects <18 years old. Critical review using Oxford Center for Evidence Based Medicine (CEBM) Critical Appraisal Tools for Prognostic Study And Systematic Review. The total number of articles identified based on the keywords used is 115 articles. Eliminating duplication with EndNote resulted in 92 articles. Furthermore, exclusion was carried out based on title and abstract so that 29 articles were filtered for which the full text was available. Of these, 23 articles did not have appropriate research questions, 3 studies did not have appropriate patient populations, and 3 articles with types that did not meet the inclusion criteria of this study. As a result, there were 4 articles that can be used in this report. Based on those four articles, it can be concluded that prophylaxis is more effective in preventing CMV disease but had more side effects, when compared to preemptive therapy. However, there was no difference in long term outcome between kidney transplant patients with CMV prophylactic or preemptive therapy.